2014
DOI: 10.3390/molecules19011353
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Neutral Polymer Bonding Agent (NPBA) as Revealed by Solid-State NMR Spectroscopy

Abstract: Neutral polymer bonding agent (NPBA) is one of the most promising polymeric materials, widely used in nitrate ester plasticized polyether (NEPE) propellant as bonding agent. The structure and dynamics of NPBA under different conditions of temperatures and sample processing are comprehensively investigated by solid state NMR (SSNMR). The results indicate that both the main chain and side chain of NPBA are quite rigid below its glass transition temperature (T g ). In contrast, above the T g , the main chain rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…[3][4][5] An alternative and less explored approachc ompares experimental chemical shift tensor principal values (i.e. [13][14][15][16] While early reportsd eriving structure from shift tensors were infrequent, the number of such studies has increased significantly in recent years [17][18][19][20][21][22][23] (Figure 1) and usually focus on organic non-peptides tructures. [2] Structural characterizations that include shift tensors are appealing because they representt hree experimental data points per nucleus and are purported to be among the most sensitive NMR parameters availablef or assessing structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] An alternative and less explored approachc ompares experimental chemical shift tensor principal values (i.e. [13][14][15][16] While early reportsd eriving structure from shift tensors were infrequent, the number of such studies has increased significantly in recent years [17][18][19][20][21][22][23] (Figure 1) and usually focus on organic non-peptides tructures. [2] Structural characterizations that include shift tensors are appealing because they representt hree experimental data points per nucleus and are purported to be among the most sensitive NMR parameters availablef or assessing structure.…”
Section: Introductionmentioning
confidence: 99%
“…Severals tudies have now demonstrated that 13 Ca nd 15 Ns hift tensors are capable of monitoring even minor variations in single crystal neutron diffractions tructures. [13][14][15][16] While early reportsd eriving structure from shift tensors were infrequent, the number of such studies has increased significantly in recent years [17][18][19][20][21][22][23] (Figure 1) and usually focus on organic non-peptides tructures. Such analyses are likely to become an NMR studies measuring chemicals hift tensors are increasingly being employed to assign structure in difficult-to-crystallize solids.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding interaction between fillers and NPBAs is highly temperature‐dependent. Glass transition temperature (T g ) of NPBA is approximately 56 °C as measured by differential scanning calorimeter (DSC) . Initially, when the premix temperature is high, side chains of NPBA is flexible and gives enhanced mobility which promotes the solubility of bonding agent into the propellant slurry.…”
Section: Bonding Agents For Nitramines Based Composite Propellantmentioning
confidence: 99%
“…As an outcome, NPBA separates from the slurry and adsorbed on the surface of nitramine. Moreover, hydroxyl functional group from the macromolecule participates in the curing process and enters into binder network to accomplish the anticipated properties .…”
Section: Bonding Agents For Nitramines Based Composite Propellantmentioning
confidence: 99%
“…Sementara contoh dari golongan polimer adalah NPBA (Neutral Polymer Bonding Agent) dan polimer amida (Liu, Sun, Hong, Pang, & Qiao, 2018). Untuk propelan berbasis HTPB, beberapa bonding agent seperti senyawa aziridine, alkanolamine, polyamine, isocyanurate, dimethyldantoin dan turunannya telah dikembangkan (Brzić et al, 2015;Hu et al, 2014).…”
Section: Abstrakunclassified